Pelatihan kematangan berkarier untuk pengambilan keputusan karier pada siswa kelas XII di SMAN 1 Kedamean - Sindi Nurmantika Putri; Awang Setiawan Wicaksono; Nadhirotul Laily (Altruis: Journal of Community Services, 2022)
SMA is a secondary education level that prioritizes the preparation of students to continue higher education or to a career path. In order for individuals to be eligible to work in a place, individuals are required to have expertise adapted to the job they want. Individuals must have career maturity in order to be able to get success and satisfaction in their work. Career maturity helps a person to gain success and satisfaction at work because his career is in accordance with his talents and interests. However, at SMAN 1 Kedamean the school has never provided guidance or training to students who wish to continue on to a career path. The school only focuses on helping and directing students who wish to continue on to higher education. Therefore, researchers are interested in providing career maturity training to class XII students who wish to continue on to a career path so that students are able to make decisions and prepare for their career choices. The training was conducted for three days and was attended by eleven students. The results obtained after the training was given were that all participants experienced improvements related to their career maturity. The training is also able to help students to make choices and make decisions regarding their desired career according to their talents and interests.